Unscrambling fluorophore blinking for comprehensive cluster detection via photoactivated localization microscopy - René Platzer (Nature Portfolio, 2020)
Determining molecular clustering in Photoactivated Localization Microscopy (PALM) experiments requires knowledge of the blinking properties of the fluorophore to prevent overcounting artefacts. Here the authors develop an experimental and analytical framework to determine the blinking parameters of fluorophores and incorporate this information into cluster analysis.